EFFECT OF PROFITABILITY, FIRM SIZE, AND CASH HOLDINGON PRACTICEINCOME SMOOTHING SECTOR CONSUMER NON-CYCLICALS - Linda Santioso; Andreas Bambang Daryatno (International Journal of Application on Economics and Business, 2026)
This study aims to determine the effect of Profitability, Firm Size, and Cash Holding on Income Smoothing Practices in the Consumer Non-Cyclical Sector. The nonprobability sampling method chosen in this study is purposive sampling, using a sample of 73 companies listed on the Indonesia Stock Exchange with an observation period of 3 years from 2021-2023. Data processing was carried out using logistic regression analysis through the SPSS application for hypothesis testing. The results revealed that Profitability and firm size have a positive direction but do not significantly influence Income Smoothing, and Cash Holding has a negative effect but does not significantly influence Income Smoothing. This means that management bonus policies, contractual obligations, or pressure from investors may have a stronger influence. In addition, regulatory pressure, ownership structure, or market conditions have a greater influence on income smoothing practices. Investors usually do not use cash holdings as a measure of company performance, there is no reason for managers to consider implementing income smoothing practices.